O ALINHAMENTO ENTRE A ESTRATÉGIA E AS COMPETÊNCIAS ORGANIZACIONAIS: UM ESTUDO DE CASO - Brida, Marinaldo de (2009)
The main objective of this study is to present and discuss the alignment between business strategies and organizational competences. From the theoretical and the experience of the company studied, this paper presents what are the characteristics of the company and how it should be an organizational environment to facilitate this alignment. As a company should proceed and what tools can be used to enable the participation of officials from all levels and areas, from planning to execution of its strategic plan and program management competences. It also shows the importance of developing competences related to strategy, called core competences. This organizational development occurs with the training of employees and the growth of their respective individual competences, promoting links between business strategies and organizational competences through individual and organizational learning.